Hardness, wear and friction characteristics of nanostructured Cu-SiC nanocomposites fabricated by powder metallurgy route. (March 2019) - Akbarpour, M.R.; Najafi, M.; Alipour, S.; Kim, H.S.
Graphical abstract: Abstract: In the present study, hardness and tribological properties of nanostructured copper reinforced with SiC nanoparticles of various volume fractions (0, 2, 4, and 6 vol%) were investigated. The nanocomposites were fabricated by high-energy mechanical milling and hot pressing method. The Cu-SiC nanocomposites showed enhanced hardness and wear resistance against WC counterface. The hardness and wear resistance of the nanocomposite increased with increasing the amount of SiC nanoparticles up to 2 vol% in the matrix, but they decreased at higher percentages of SiC (4 and 6 vol%). Flake formation-spalling and abrasion were identified as the predominant wear mechanisms. It was found that reducing the normal load and increasing the amount of SiC resulted in an increase in the friction coefficient of the nanocomposite.